Examining What Works for High Risk Youth Involved in the Juvenile Justice System: Comparing the Effect of the Community Connections (CC) Program to Intensive Supervision Probation (ISP) Over A Nine-Year Time Period (Journal of Applied Juvenile Justice Services, 2020)
Using administrative data collected by an urban juvenile probation department between January 2007 and August 2016, this study compared the impact of the Community Connections (CC) program to a matched sample of youth who received intensive supervision probation (ISP) on six time-to-event variables (i.e., time to second program, detention, out-of-home placement, another offense, violation of court order, and days in program). The study included youth who were assigned to court-ordered post-adjudication community supervision and who were deemed to have a high risk of re-offending by the department’s risk and needs assessment. CC and ISP youth were matched using propensity score matching that created a final sample of 381 youth in each program. When examining the program effect of CC vs. ISP on the time-to-event variables the findings were mixed. However, across both programs, the analysis revealed that youth who remained in the programs longer and youth with a successful program discharge generally experienced better long-term outcomes than their peers.